Design and Hardware Implementation of a Speech Cipher System - Ameen, Siddeeq Y.; Al-Shalchi, Abbas A.; Al-Bayati, Muhanad D. (Nahrain University College of Engineering Journal, 2008)
Digital ciphering of speech signals based on one of modern cryptography algorithms, called the Rijndael algorithm, is studied and presented in this paper. The algorithm meets most of the requirements of security level in recent applications. A system to encrypt speech files recorded with Sound Blaster Card of a personal computer was proposed and simulated successfully using MATLAB® language. Subjective measure and objective measure using segmental spectral signal-to-noise ratio, were used to test the proposed system performance. In these tests residual intelligibility of the encrypted speech and quality of the recovered speech were calculated and assessed. Finally, a hardware implementation of the above cipher system has been proposed using the TMS320-C30. The real time requirements from the speech cipher system have been computed in terms of execution time together with factors affecting such implementation. The results show the capability of the cipher system to be implemented using the DSP device suggested. Furthermore, the results of hardware implementation also show the security of the system is very close to that of the simulated version.